2021
DOI: 10.2337/db21-0251
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy Suppresses Hepatic Glucose Production and Increases Hepatic Insulin Clearance Independent of Weight Loss

Abstract: Bariatric operations induce weight loss, which is associated with an improvement in hepatic steatosis and a reduction in hepatic glucose production. It is not clear whether these outcomes are entirely due to weight loss, or whether the new anatomy imposed by the surgery contributes to the improvement in the metabolic function of the liver. We performed vertical sleeve gastrectomy (VSG) on obese mice provided with a high-fat high-sucrose diet and compared them to diet and weight-matched sham-operated mice (WMS)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…To date, there is no reliable rodent model for sporadic AD which is the more common form of AD. We and others have shown that SG is not effective in maintaining weight loss in early-onset genetic obesity modeled by db/db mice or Melanocortin 4 Receptor null rats, yet it is effective in obesity models induced through a calorie-rich diet ( Hatoum et al, 2012 ; Abu-Gazala et al, 2018 ; Ben-Haroush Schyr et al, 2021 ). Our data, therefore, do not reject the hypothesis that SG can have a weight loss independent effect in sporadic AD in patients, and that this effect cannot overcome the strong genetic basis of disease in 5xFAD mice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, there is no reliable rodent model for sporadic AD which is the more common form of AD. We and others have shown that SG is not effective in maintaining weight loss in early-onset genetic obesity modeled by db/db mice or Melanocortin 4 Receptor null rats, yet it is effective in obesity models induced through a calorie-rich diet ( Hatoum et al, 2012 ; Abu-Gazala et al, 2018 ; Ben-Haroush Schyr et al, 2021 ). Our data, therefore, do not reject the hypothesis that SG can have a weight loss independent effect in sporadic AD in patients, and that this effect cannot overcome the strong genetic basis of disease in 5xFAD mice.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical and animal studies demonstrated that these effects are mediated by weight loss dependent and independent mechanisms ( Chambers et al, 2011 ; Sjostrom, 2013 ; Douros et al, 2019 ; Aminian et al, 2021 ; Azulai et al, 2021 ). Some of the positive and negative effects of bariatric surgery were observed also in lean rodents, suggesting that the metabolic and endocrine state induced by surgery can have beneficial or detrimental physiolgoical effects ( Li et al, 2019 ; Ben-Haroush Schyr et al, 2021 ; Akalestou et al, 2022a ; Hefetz et al, 2022 ). Obesity is associated with cognitive decline and is a risk factor for AD ( Ahlskog et al, 2011 ; Ngandu et al, 2015 ; Spitznagel et al, 2015 ; Rochette et al, 2016 ; Stephen et al, 2017 ), and bariatric surgery was shown in most studies to improve cognitive function in patients with obesity ( Miller et al, 2013 ; Alosco et al, 2014a , b ; Spitznagel et al, 2015 ; Rochette et al, 2016 ; Thiara et al, 2017 ; Prehn et al, 2020 ; Morledge and Pories, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the findings that lipolysis-derived NEFA repress hepatic CEACAM1 expression, consistent with findings in rats exposed to acute intralipid infusion [ 72 ]. Accordingly, hepatic insulin clearance and insulin sensitivity were restored in diet-induced mouse models of obesity undergoing Vertical Sleeve Gastrectomy in parallel to inducing the expression of CEACAM1 and IDE, and independently of weight loss [ 96 ].…”
Section: Elevated Plasma Nefa Play a Primary Role In Hepatic Insulin ...mentioning
confidence: 99%
“…Sleeve gastrectomy (SG) is a common bariatric surgery wherein most of the stomach is excised along the greater curvature to produce a sleeve-shaped stomach. This surgery leads to weight loss and improved glycemic control, and alleviation of metabolic disorders in most patients and rodent models (19)(20)(21)(22)(23). SG affects the microbiome, the levels of bile acids and other metabolites in the blood, and leads to a post-prandial increase in GI and pancreatic hormones such as Glp1 and insulin and modulates processes that regulate systemic metabolism (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%